The theory of global imbalances: mainstream economics vs. structural Keynesianism - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
Prior to the 2008 financial crisis there was much debate about global trade imbalances. Prima facie, the imbalances seem a significant problem. However, acknowledging that would question mainstream economics' celebratory stance toward globalization. That tension prompted an array of explanations which explained the imbalances while retaining the claim that globalization is socially beneficial. This paper surveys those new theories. It contrasts them with the structural Keynesian explanation that views the imbalances as an inevitable consequence of neoliberal globalization. The paper also describes how globalization created a political economy that supported the system despite its proclivity to generate trade imbalances.
urn:nbn:de:101:1-201411242601
Keywords: F02; F32; F33; 330; global imbalances; saving glut; new Bretton Woods; asset shortage; structural Keynesianism